Network Meta-Analysis of Open Reduction Internal Fixation, Intramedullary Nail Fixation, and Distal Femoral Replacement for Periprosthetic Distal Femur Fractures - Lu, Yao; Xu, Yibo; Ren, Cheng; Wang, Qian; Sun, Liang; Zhang, Chengcheng; Huang, Qiang; Xue, Hanzhong; Li, Zhong; Zhang, Kun; Zhao, Yang; Ma, Teng (Frontiers in Materials, 2022)
Background: Although open reduction internal fixation (ORIF) with periarticular locking plates, retrograde intramedullary nail (IMN) fixation, and distal femoral replacement (DFR) have been widely used for treatment of periprosthetic distal femur fractures (PPDFF), it remains unclear which one may be optimal surgical strategy. Objective: This network meta-analysis aimed to determine the optimal surgical strategy for PPDFF from ORIF, IMN and DFR through evaluating major complications rates and revision rates. Patients and Methods: We identified eligible studies through performing an updated literature search in PubMed, Embase and the Cochrane Central Register of Controlled Trials (CENTRAL) and checking published meta-analyses. The methodological index for non-randomized studies (MINORS) was used to assess the methodological quality of eligible studies. Major complications and revision rates were defined outcomes of interesting. All statistical analyses were performed using ADDIS 1.4 software. Results: We included 17 eligible studies into the final analysis. Statistical analyses did not reveal significant differences when ORIF compared with IMN, ORIF compared with DFR, and IMN compared with DFR in terms of two clinical outcomes. However, DFR achieved a beneficial trend in major complications (odds ratio [OR]=1.34, 95%CrI=0.48 to 3.80) and revision (OR=1.64, 95%CrI=0.68 to 4.38) rates compared with IMN. Ranking probabilities indicate that DFR has the highest probability of being optimal option, followed by ORIF and IMN. Conclusions: There was no difference in major complications or reoperations between the three treatments. However, ORIF with periarticular locking plates may be a preferred alternative option because DFR is limited by high cost. Moreover, our study highlights the need for future prospective trials evaluating the outcomes of these three surgical strategies.